Gestão escolar e formação do pedagogo: relações e implicações a partir da análise de projetos político-pedagógicos de universidades públicas - Barbosa, Andrea Haddad [UNESP]; Abdian, Graziela Zambão [UNESP] (Universidade Federal de Minas Gerais (UFMG), Faculdade de Educação, 2013)
The literature has pointed out the educational deficits of Brazilian public schools, the complexity of school management, and the need for better qualification for the exercise of this function. Considering this perspective, the present research questions: How is school management being contemplated within the initial pedagogical training in the state of Paraná? In this sense, this article aims to survey and analyze how school management in professional training in public universities Educator of Paraná is being contemplated after the publication of the National Curriculum Guidelines for the Education Course (DCNP). The study works with a qualitative approach to carry out, in the one hand, the bibliographic survey and systematization and, on the other hand, the survey, systematization and analysis of some elements in the political-pedagogical projects of different public universities. The data collected in six public universities show a significant oscillation between the workload aimed at the knowledge of School Administration and a variety of covered contents. Such differences may reflect the scope of the National Curriculum Guidelines as well as the present theoretical dispersion regarding the current knowledge on School Administration.

A literatura tem apontado os déficits educacionais da escola pública brasileira, a complexidade dos processos de gestão escolar e a necessidade de melhor qualificação profissional para o exercício da função do gestor. Considerando tal perspectiva, esta pesquisa questiona: Como está sendo contemplada a gestão escolar no âmbito da formação inicial do pedagogo no Estado do Paraná? Nesse sentido, este artigo tem o objetivo de levantar e analisar como está sendo contemplada a gestão escolar na formação do profissional pedagogo nas universidades públicas do Paraná, após a publicação das Diretrizes Curriculares Nacionais para o Curso de Pedagogia (DCNP). O estudo trabalhou com a abordagem qualitativa ao realizar levantamento e sistematização bibliográfica e o levantamento, sistematização e análise de alguns elementos contidos nos projetos político-pedagógicos de diferentes universidades públicas. Os dados revelam uma oscilação significativa entre a carga horária destinada aos conhecimentos de Administração Escolar e uma diversidade de conteúdos abordados. Tais diferenças podem estar refletindo a abrangência das Diretrizes Curriculares Nacionais como também a dispersão teórica atual dos conhecimentos em Administração Escolar.
School management and pedagogue training: relationships and implications from the analysis of political-pedagogical projects of public universities
Keywords: Formação do Pedagogo; Administração Escolar; Projeto Político-Pedagógico; Training of pedagogues; School Administration; Political-Pedagogical Project